The diet of feral cats at New Island, Falkland Islands, and impact on breeding seabirds - Matias, Rafael (2012)
We studied the diet of feral cats (Felis catus) on New Island, Falkland Islands, through the analysis of 373 scats collected during the austral summers of 2004/2005 and 2005/2006. The most frequent prey were three introduced mammals (house mice Mus musculus, ship rats Rattus rattus and rabbits Sylvilagus sp.) and the thin-billed prion Pachyptila belcheri (each season present on ca. 21% of the analysed scats). These represent the Wrst systematic data on feral cat diet for the Falklands. A simple bioenergetics model suggests that cats could be eating in the region of 1,500–11,000 prions per season, representing <1% of the local adult and subadult population. Predation on other seabirds nesting on New Island (several penguin species, albatrosses and cormorants) was unimportant, with the possible exception of white-chinned petrels Procellaria aequinoctialis, which nest locally in very small numbers. For each prion eaten, cats were estimated to have killed 1.1–1.9 ship rats during the summer season, and probably more in autumn and winter. Knowing that ship rats are prion predators, it is conceivable that, on the whole, cats are having a positive impact on the prion population, a scenario predicted by general theoretical models. Thus, considering the available information, we would not recommend the implementation of any eradication programme on New Island that would target cats in isolation. Nevertheless, it would be prudent to consider some local action targeting cats and rats around the small New Island white-chinned petrel colony.